Recent Updates of Helicobacter pylori Infection: from Epidemiology Study to Guideline Issues - Laurentius A Pramono; Ari Fahrial Syam (The Indonesian Society for Digestive Endoscopy, 2014)
Helicobacter pylori (H. pylori) infection is still a big issue in gastroenterology field. Its relationship withgastrointestinal malignancies now is widely known and the extra-gastrointestinal manifestation of this epidemicbring new problems. Although the prevalence is decreasing in developed countries, the resistance rate of somestrains to standard therapy needs more attention and new strategies. Recent epidemiology studies revealed that H. pylori infection is a specific population disease. Many trials and meta analyses revealed new evidences and horizons in the management of this infection. This review updated and highlighted pathophysiology, clinicalaspect, and new epidemiology data on H. pylori infection which is published in the last five years.Keywords: Helicobacter pylori, update, epidemiology ABSTRAKInfeksi Helicobacter pylori (H. pylori) masih merupakan permasalahan besar di bidang gastroenterologi.Hubungannya dengan keganasan saluran cerna saat ini telah dikenal secara luas dan manifestasinya di luarpencernaan pada epidemi ini membawa masalah baru. Meskipun prevalensinya menurun di negara-negara maju,namun tingkat resistensi dari beberapa terapi standar membutuhkan lebih banyak perhatian dan strategi baru.Penelitian epidemiologi baru-baru ini mengungkapkan bahwa infeksi H. pylori didapatkan pada populasi tertentu.Banyak percobaan dan metaanalisis yang mengungkapkan bukti dan wawasan baru dalam penatalaksanaannya.Ulasan ini memperbarui dan menyoroti patofisiologi, aspek klinis, dan data epidemiologi baru pada infeksi H.pylori yang telah dipublikasikan dalam lima tahun terakhir.Kata kunci: Helicobacter pylori, memperbarui, epidemiologi